Analisis Program Pemberian Makanan Tambahan Terhadap Status Gizi Balita sebagai Upaya Pencegahan Stunting - Anggraini, Dwi; Sirojuddin Ibnu Nur; Yayuk Widyastuti Herawati (Jurnal Makkareso, 2024)
Supplementary Feeding (PMT) is an activity of providing food to toddlers who have a nutritionally deficient status in the form of food that contains nutrients according to their needs. In the research on the analysis of the supplementary feeding program on the nutritional status of toddlers as an effort to prevent stunting in Posyandu Kesamben Hamlet, Kesamben Village, Ngajum District, Malang Regency using the Participatory Action Research (PAR) method. In addition, this research was also conducted by presenting a complete picture of the form of Posyandu services in Kesamben Hamlet which aims to observe and observe specifically with the target target in the form of supplementary feeding programs on the nutritional status of toddlers. The results of research conducted at the three Posyandu can be seen that there are three children who are at risk of stunting and one child has a stunting status. Aside from the four toddlers, all toddlers can be potentially stunted, so additional food is given as an effort to prevent stunting.